Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/nature01046
|View full text |Cite
|
Sign up to set email alerts
|

Competence to replicate in the unfertilized egg is conferred by Cdc6 during meiotic maturation

Abstract: Meiotic maturation, the final step of oogenesis, is a crucial stage of development in which an immature oocyte becomes a fertilizable egg. In Xenopus, the ability to replicate DNA is acquired during maturation at breakdown of the nuclear envelope by translation of a DNA synthesis inducer that is not present in the oocyte. Here we identify Cdc6, which is essential for recruiting the minichromosome maintenance (MCM) helicase to the pre-replication complex, as this inducer of DNA synthesis. We show that maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…The Cdc6 antisense oligonucleotides used in our study has previously been shown to specifically knockdown Cdc6 mRNA and thus Cdc6 protein in Xenopus oocytes. 6 The specificity of Cdc6 antisense oligonucleotides to inhibit Cdc6 protein expression during maturation was further confirmed by protein gel blot analysis (Fig. S2).…”
Section: Resultsmentioning
confidence: 87%
“…The Cdc6 antisense oligonucleotides used in our study has previously been shown to specifically knockdown Cdc6 mRNA and thus Cdc6 protein in Xenopus oocytes. 6 The specificity of Cdc6 antisense oligonucleotides to inhibit Cdc6 protein expression during maturation was further confirmed by protein gel blot analysis (Fig. S2).…”
Section: Resultsmentioning
confidence: 87%
“…Accumulation of principal replication licensing factors (the proteins of ORC and MCM complexes) was demonstrated in fullygrown and maturing amphibian (Lemaitre et al, 2002;2004;Whitmire et al, 2002) and human (Eward et al, 2004) oocytes. In these studies particular protein fractions (soluble vs. insoluble proteins) were not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably why the ovarian oocytes lack of certain components of pre-RC complexes such as the Cdc6 protein, which is involved in the loading of the MCM proteins on to chromatin. Cdc6 protein is absent in the nuclei of fully-grown oocytes of Drosophila, Xenopus and mouse and is not synthesized before the initiation of maturation (Lemaître et al, 2002;2004;Whitmire et al, 2002, Anger et al, 2005. In contrast, another component of pre-RC complex, the Mcm2 protein, was shown to be stored in the nuclei of fully-grown mouse oocytes (Lemaître et al, 2004).…”
Section: Mcm2 6 and 7 In Mouse Oocytes And One-cell Embryo 289mentioning
confidence: 99%
“…To understand how the competence for the DNA replication is built in the activated oocyte it is necessary to know whether the proteins of pre-RC are available in oocytes. The Mcm2-7 proteins have been recently found in the fully-grown oocytes of Xenopus (Whitmire et al, 2002, Lemaître et al, 2002. The Mcm2 protein was found in the fully-grown oocytes of mouse and Drosophila (Lemaître et al, 2004) and in the primary human oocytes (Eward et al, 2004).…”
mentioning
confidence: 99%